Analisis Kasus Pelanggaran Etika Akuntan Pada Perusahaan E-Fishery Dalam Perspektif Maqashid Syariah - Nikmah, Ajeng Nafilatun; Putri Safrina, Dessy; Khofidhotul, Nur; Lestari, Retnotia Dwi; Misidawati, Dwi Novaria (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2025)
Almost every job requires its workers to be ethical in doing everything. In the last two decades, financial scandals in the form of misrepresentation and fraud by accountants and accounting firms have increased significantly, one of the cases of ethical violations and fraud is the case carried out by eFishery management. Based on the eFishery case, the management has committed an ethical violation because they manipulated various information such as income information, profit information, and asset information. This study aims to find out more about the case of ethical violations involving the management of the eFishery company, especially violations of accountant ethics using an Islamic perspective, namely maqashid sharia. The method used is a qualitative method where the results will be presented in descriptive form, using an evaluation approach with the aim of collecting relevant information. The case of violation of accountant ethics at the e-Fishery company shows that the manipulation of financial reports carried out by e-Fishery management violates the principles of maqashid sharia, especially in terms of assets (al-mal), trust and integrity (ad-din), reason (al-aql), soul (an-nafs), and descendants (an-nasl). This case will have a significant impact on investor losses financially, but also reduce public confidence, weaken the attractiveness of technology investment in Indonesia, and raise concerns about the integrity of the startup ecosystem.